Hands Percussion of Malaysia: Performing Cosmopolitanism Built on Shared Philosophy and Artistic Values in Global Musical Alliances - Clare Suet Ching Chan, (Wacana Seni Journal of Arts Discourse, 2019)
Hands Percussion is a percussion ensemble in Malaysia that integrates percussive rhythm, creative movement and spectacular choreography with diverse musical sounds. Founded in 1997, Hands Percussion has evolved from a Chinese drumming ensemble to a contemporary performing arts ensemble that embraces a myriad of local and global musical styles and movements. This article explores Hands Percussion's identity from local to cosmopolitan musicians, whose opportunities for musical alliances are enhanced through international connections and collaborations. While Hands Percussion is exposed to diverse global musical styles, I argue that their choices for global musical alliances are founded upon three shared philosophies and artistic values including: (1) virtuosity and skill, (2) philosophy of life and artistic values, and (3) openness, flexibility and passion toward learning. Through interviews with Hands Percussion artistic directors and performers, this article examines the shared philosophies and artistic values that enable successful global alliances, consequently constructing the "cosmopolitanism" in their performances.